2014
DOI: 10.1097/hjh.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

Aortic pulse wave velocity predicts mortality in chronic kidney disease stages 2–4

Abstract: These results provide the first direct evidence that in patients with CKD stage 2-4, increased aortic stiffness determined by aPWV is a strong independent predictor of all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 56 publications
2
38
2
Order By: Relevance
“…No association was shown between baseline aortic stiffness and GFR decline in a mixed model regression analysis [46]. The same observation was made by Baumann et al [51] in a cohort of 135 CKD patients (mean follow-up 42 months, mean eGFR 41.1 ml/min/1.73 m 2 ). On the other hand, in a prospective cohort (follow-up 1.5 years) of 120 patients (mean age 69 ± 12 years) at stages 3-4 CKD (baseline eGFR 32 ± 11 ml/min/1.73 m 2 ), aortic PWV was significantly associated with the gradient of reciprocal creatinine plot, monitoring change in eGFR.…”
Section: Impact Of Aortic Stiffness On Ckd Progressionsupporting
confidence: 56%
“…No association was shown between baseline aortic stiffness and GFR decline in a mixed model regression analysis [46]. The same observation was made by Baumann et al [51] in a cohort of 135 CKD patients (mean follow-up 42 months, mean eGFR 41.1 ml/min/1.73 m 2 ). On the other hand, in a prospective cohort (follow-up 1.5 years) of 120 patients (mean age 69 ± 12 years) at stages 3-4 CKD (baseline eGFR 32 ± 11 ml/min/1.73 m 2 ), aortic PWV was significantly associated with the gradient of reciprocal creatinine plot, monitoring change in eGFR.…”
Section: Impact Of Aortic Stiffness On Ckd Progressionsupporting
confidence: 56%
“…Cheng et al 18 conducted a meta-analysis of six cohort studies and reported an increased risk of atrial fibrillation with 1°HB. There are two additional studies in our review, Perez et al 14 and Uhm et al 16 and both of these studies suggest an increased risk of atrial fibrillation with 1°HB. We build upon this review by including the other outcomes mortality, cardiovascular mortality, heart failure, coronary heart disease and stroke.…”
Section: Discussionmentioning
confidence: 78%
“…Out of the 879 studies retrieved from the search, 26 studies were relevant but 12 studies were excluded from the analysis (see online supplementary table S1). A total of 14 studies4 10–17 19–23 were included: 12 general population studies, 1 cohort with coronary heart disease19 and 1 cohort with hypertension 16…”
Section: Resultsmentioning
confidence: 99%
“…in his work showed that among 3816 patients with hypertension the number of patients with atrioventricular block stage 1 was 14.3 %. It was demonstrated that atrioventricular block stage 1 is an independent factor in the future development of AF and left ventricle dysfunction in these patients [18]. Iskenderov B.G.…”
Section: Resultsmentioning
confidence: 99%